Subglottic perioperative airway—tube inflation via randomized evaluation with variable syringe size (Spair‐Tire) study. (27th January 2019) - Williams, George W.; Artime, Carlos A.; Mancillas, Omar L.; Syed, Tariq A.; Burnett, Tyrone; Graham, Russell; Tam, Jason; Hagberg, Carin A.
Abstract: Introduction: Risks of endotracheal tube cuff (ETTC) over inflation must be balanced with the need to achieve a minimum pressure of 20 cm H2 O. Methods have been developed to estimate adequate ETTC pressurization but do not provide accurate endotracheal tube cuff pressure (ETCP) measurements. Hence, different sized syringes may play a role in determining ETCP. Objectives: Determine optimal syringe size for recommended ETCP. Methods: Two hundred patients were randomized to use of either a 10‐mL syringe (standard syringe) or a 5‐mL syringe (study group) for ETTC inflation. Following the insertion of the endotracheal tube, the ETTC was inflated per the attending anesthesiologist. Within 10 minutes of intubation, ETCP was measured with a hospital‐provided manometer. Results: The percentage of in range cuff pressures for the 5‐mL group was 10.53% and 6.78% for the 10‐mL group. 84.21% ( n = 64) of the study group and 91.53% ( n = 54) of the control group had cuff pressures exceeding 30 cmH2 O. Although our study did not demonstrate that syringe size was predictive of ideal cuff pressure ranges, the average cuff pressure for the 5‐mL group was 55.8 cm H2 O versus 68.8 cm H2 O in the 10‐mL group. Conclusion: Although both 5‐ and 10‐mL syringes resulted in elevated cuff pressures after intubation, 5‐mL syringes resulted in a lower degree of elevation. Use of a 5‐mL syringe should be considered when inflating the endotracheal cuff to possibly reduce patient harm secondary to elevated cuff pressures. Further studies assessing smaller syringe sizes to reduce cuff pressures are warranted.